Determination of the rheological properties of thin plate under transient vibration - Jan Skočilas; Blanka Skočilasová; Josef Soukup (Latin American Journal of Solids and Structures)
The article deals with systematic analysis of the transient vibration of rectangular viscoelastic orthotropic thin 2D plate. The analysis is focused on specific deformation models of plate and for specific linear models of rheological properties. The viscoelastic isotropic and anisotropic (orthotropic) materials were investigated. The plate is loaded by general transient impulse. The time and coordinate dependencies of the fundamental quantities - displacements, rotations, stress and deformations in arbitrary points of plate under transient vibration, e. g. the analysis of stress and deformation waves in plates were investigated. The selected models are defined by constitutive equations for stress and deformation dependence. The isotropic and orthotropic model is considered. The analysis results depend on quality of the determined mechanical properties of the materials. The standard methods commonly used are time-consuming and not accurate enough. The new methodology of determining the material parameters directly from investigated plate is proposed and proven.